Peran Guru Akidah Akhlak dalam Menanamkan Nilai Kejujuran pada Siswa Kelas VIII A MTs Hidayatul Mubtadiin Desa Sidoharjo Jati Agung Lampung Selatan - Eka Sinta Mulita; Riskun Iqbal; Ayu Aristika (Journal on Education, 2024)
This exploration expects to depict: 1) What is the job of the moral aqidah educator in imparting the worth of trustworthiness in class VIII An understudies at Madrasah Hidayatul Mubtadiin for the 2022/2023 scholarly year. 2) What are the repressing and empowering factors for educators of moral convictions in imparting the worth of trustworthiness in class VIII An understudies at Madrasah Hidayatul Mubtadiin for the 2022/2023 scholastic year. This kind of exploration is subjective field research (field research) with the idea of subjective distinct examination, and the idea of this exploration is subjective spellbinding, to be specific orderly, verifiable and exact perusing of circumstances and occasions. Information sources are research subjects that have a significant position, acquired from essential and auxiliary information sources. The information assortment procedure is perception, meetings and documentation. Information legitimacy checking procedure utilizing triangulation methods. In the interim, information examination utilizes information decrease, introducing information and making determinations. The aftereffects of this exploration show that: 1). The job of the educator of moral convictions in imparting the worth of trustworthiness in understudies is by utilizing two techniques, immediate and circuitous. The immediate technique is by utilizing the strategy for instance, adjustment, management, guidance and discipline. In the mean time, the aberrant way is by learning in classes. 2). In the mean time, the restraining factors for imparting the worth of trustworthiness in understudies through Islamic otherworldly extracurricular exercises are; A few understudies are moves on from state funded schools and have family foundations that need strict information, so they require additional consideration from educators in giving direction to these understudies. Understudies feel fatigue in light of the fact that the exercises are repetitive. There are a few instructors who don't uphold the most common way of surveying understudies' genuineness. Generally speaking, from the exploration results, the endeavors of Akidah Akhlak educators have been very fruitful in surveying understudies' genuineness, as confirmed by the exercises and strategies that have been applied from the aftereffects of meetings and perceptions in the field.